[tex]f:( - 1;∞) \: - > R, \: f(x) = 1 - 2x + 2 ln(x + 1) [/tex]
[tex]Le \: luăm \: pe \: rând:[/tex]
[tex]1' = 0[/tex]
[tex](2x)' = 2 \times 1 = 2[/tex]
[tex](2 ln(x + 1) )' = 2 \times \frac{1}{x + 1} = \frac{2}{x + 1} [/tex]
[tex]Acum \: calculăm \: f'(x):[/tex]
[tex]f'(x) = 0 - 2 + \frac{2}{x + 1} = - 2 + \frac{2}{x + 1} [/tex]
[tex]Amplificăm \: -2 \: cu \: (x+1 \: ) și \: obținem:[/tex]
[tex]f'(x) = \frac{ - 2(x + 1) + 2}{x + 1} = \frac{ - 2x - 2 + 2}{x + 1} [/tex]
[tex]f'(x) = \frac{ - 2x}{x + 1} [/tex]